Assessment of the ESC quality indicators in patients with acute myocardial infarction: a systematic review. Issue 8 (21st June 2021) - Rossello, Xavier; Massó-van Roessel, Albert; Perelló-Bordoy, Antoni; Mas-Lladó, Caterina; Ramis-Barceló, Maria F; Vives-Borrás, Miquel; Pons, Jaume; Peral, Vicente
Abstract: Aims: To help improving quality of care in patients with acute myocardial infarction (AMI), the European Society of Cardiology (ESC) set 20 quality indicators (QIs). There is a need to compile and summarize QI availability, feasibility, and global compliance in real-world registries. Methods and results: A systematic review of PubMed and Web of Science was conducted including all original articles reporting the use of the ESC QIs in AMI patients. Methods and reporting follow the guidelines of the PRISMA Statement and the protocol was registered in PROSPERO (CRD42020190541). Among the 220 screened citations, 9 studies met the inclusion criteria after full-text review. Among these 9 studies, there were 11 different cohorts. Patients were recruited from three different continents (31 countries). The number of QIs assessed ranged from 6 to 20, with 5 studies (56%) reporting data for at least 75% of the 20 QIs. There were room for improvement in terms of data availability (i.e. domain 6 measuring patient's satisfaction), feasibility (i.e. difficulties to find all data for composite QIs in domain 7), and attainment (i.e. high levels of compliance with the percentage of reperfused ST-segment elevation myocardial infarction patients, but low levels for a timely reperfusion). Conclusions: Our systematic review has shown that it is possible to measure most QIs in existing registries, and that there is room for improvement in terms of data availability, feasibility, and levels of attainment to QIs. Our findings may influence the design of future registries to capture this information and help in QIs definition updates. Graphical abstract: